Intellectual content of short films in light of the objectives of art education (Journal of the College of Basic Education, 2025)
Cinema is a double-edged sword, as it can contribute to building and developing the human being, or it can be directed as a tool to destroy societies and distort the values ​​of their individuals. To reduce this problem and ensure that its educational role is invested in educational institutions, this study came with the aim of revealing the intellectual content of short films participating in the annual competition held by the Ministry of Education in 2022 AD, amounting to (15) films. The researcher randomly chose (3) films from them as a sample for his research. He also chose the descriptive-analytical approach, due to its suitability for the procedures of this research. He designed a form to analyze the films in light of the objectives of art education. Through the use of statistical methods, represented by frequency tables and percentages, to ensure the validity of the form paragraphs and the (Holste) equation to extract its stability coefficient, he concluded that the percentage of non-appearance of the form paragraphs in the three sample films is not insignificant, especially since the percentage of appearance was very modest and not encouraging. The most important conclusions are the directors and scriptwriters were not directed by the organizing body of this competition to work in light of the objectives of art education.